Political legitimacy and housing : stakeholding in Singapore - Chua, Beng Huat. (London ; New York : Routledge, 1997)
Looking at the ways in which Singapore's planners have dealt with the problems of creating communities in a modern urban environment, the author concludes that the success of the public housing programme has done much for the nation. Singapore's successful public housing programme is a source of political legitimacy for the ruling People's Action Party. Beng-Huat Chua accounts for the success of public housing in Singapore and draws out lessons for other nations. Housing in Singapore, he explains in this incisive analysis, is seen neither as a consumer good (as in the US) nor as a social right (as in the social democracies of Europe). The author goes on to look at the ways in which Singapore's planners have dealt with the problems of creating communities in a modern urban environment. He concludes that the success of the public housing programme has done much for Singapore.
1. Public-housing policies compared : United States, ex-socialist nations and Singapore -- 2. From city to nation : planning Singapore -- 3. Resettling a Chinese village : a longitudinal study -- 4. Modernism and the vernacular : public spaces and social life -- 5. Adjusting religious practices to different house-forms -- 6. A practicable concept of community in a high-rise housing environment -- 7. Public housing and political legitimacy -- 8. Nostalgia for the kampung.
Includes bibliographical references (pages 174-180)-and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Public housing -- Singapore; Public housing -- Government policy -- Singapore; City planning -- Singapore; Logement social -- Singapour; Logement social -- Politique gouvernementale -- Singapour; SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Infrastructure; City planning; Public housing; Public housing -- Government policy; Singapore